AD, Volume 11, n° 1, 1986 - Full Issue - journal system (Africa Development, 1986)
CONTENTS La dépendance en héritage au Burkina Faso L'économie avant la révolution Kamadini OUALI ....................... 5 Technology policy and planning in t The case of Food, Agriculture and Energy in Tanzania Hasa Mfaume MLAWA ....................... 47 The informal sector in the labour reserve economies of Southern Africa with special reference to Zimbabwe Thandika MKANDAWIRE ........................ 61 L'exploitation des ressources uranifères namibiennes et la politique nucléaire de l'Afrique du Sud Smail KHENNAS .......................... 83 Perspectives on the development of electronics technology: The implications for dependent capitalist economies Gloria THOMAS-EMEAGWALI ....................... 97 The crisis in the public sector: The case of Morocco Habib EL MALKI ............................ 109 BOOK REVIEW-REVUE DES LIVRES The story of an African Working class: Ghanaian Miners' Struggles 1870-1980 by Jeff Grisp Wilbert B.L. KAPINGA ........................ 127 FOCUS ON RESEARCH AND TRAINING INSTITUTES PLEINS FEUX SUR LES INSTITUTS DE RECHERCHE ET DE FORMATION. - Le Centre d'Etude Socio-economique (Guinée Bissau) - Centre de Documentation, de Recherches et de Formation Indianocéaniques, Ile Maurice ................. 133